2015
DOI: 10.1002/2014jd022838
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiometer observations of interannual water vapor variability and vertical structure over a tropical station

Abstract: The intraseasonal and interannual characteristics and the vertical distribution of atmospheric water vapor from the tropical coastal station Thiruvananthapuram (TVM) located in the southwestern region of the Indian Peninsula are examined from continuous multiyear, multifrequency microwave radiometer profiler (MRP) measurements. The accuracy of MRP for precipitable water vapor (PWV) estimation, particularly during a prolonged monsoon period, has been demonstrated by comparing with the PWV derived from collocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…In contrast to traditional remote sensing techniques, the use of GPS to sense water vapor is advantageous, in the sense that it is of high accuracy, has all-weather capability, has high spatial temporal resolution, and is cost effective. Therefore, GPS-PWV data have been widely used across meteorology and climatology communities, e.g., numerical weather prediction (NWP), water vapor tomography, and severe weather prediction [Bosy et al, 2010;Dai et al, 2002;Gendt et al, 2004;Jade and Vijayan, 2008;Li et al, 2014;Renju et al, 2015;Shoji et al, 2011;Song et al, 2006;Vey et al, 2010;Zhang et al, 2015]. With the advent of multiple Global Navigation Satellite Systems (GNSS), e.g., the modernization of GPS and GLONASS as well as the two new emerging constellations BeiDou and Galileo [Tan et al, 2016], the next generation of GNSS will have more potential to serve the needs of meteorology applications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional remote sensing techniques, the use of GPS to sense water vapor is advantageous, in the sense that it is of high accuracy, has all-weather capability, has high spatial temporal resolution, and is cost effective. Therefore, GPS-PWV data have been widely used across meteorology and climatology communities, e.g., numerical weather prediction (NWP), water vapor tomography, and severe weather prediction [Bosy et al, 2010;Dai et al, 2002;Gendt et al, 2004;Jade and Vijayan, 2008;Li et al, 2014;Renju et al, 2015;Shoji et al, 2011;Song et al, 2006;Vey et al, 2010;Zhang et al, 2015]. With the advent of multiple Global Navigation Satellite Systems (GNSS), e.g., the modernization of GPS and GLONASS as well as the two new emerging constellations BeiDou and Galileo [Tan et al, 2016], the next generation of GNSS will have more potential to serve the needs of meteorology applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RH profiles derived from 6-hourly radiosonde ascents for the entire period are also available. Similar information for the same period has also been available from Thiruvananthapuram, a coastal station at the southern tip of Indian peninsula 145 . Synthesizing data from all these, Feng et al 18 have shown that there is a substantial dry bias within the boundary layer, in the model (WRF-CHEM) predicted RH under certain conditions, which could lead to an underestimation of AOD in the model.…”
Section: Relative Humidity Profiles and Its Effect On Aodmentioning
confidence: 78%
“…The variability during wet season ranged from 4 mm to 8 mm even so PWV is high while during wet season, although PWV is low, it has high variability that ranged from 6 mm to 12 mm. This indicates that during wet season especially during peak of the SW monsoon and typhoon season in the area, whereas there is occasional increase in moisture due to sporadic weather events such as localized thunderstorms may have contributed to the high variability of PWV during dry season [22][23][24].…”
Section: Resultsmentioning
confidence: 95%